Urban Displacement In Malaysia: A Social-Legal Analysis - Rahim, Rohani Abdul; Bakar, Kamarudin Abu; Tajuddin, Muhammad Afiq Ahmad (Universiti Sains Malaysia, 2016)
Urbanization has caused the people to be victimized, marginalize, discriminated, their right denied and finally displaced. Development-caused displacement (DIDR) is a highly diverse global social problem that occurred worldwide and addressed in humanitarian base approach or right based approach. This dilutes the real issue that citizen are victimize and marginalize in the course of realizing the development induced onto the people. Vulnerabilities emerge through rapid urbanization that resulted in conflict when urban violence, psychosocial health and gender‐based violence become more obvious. For purpose of human security, people should be allows for a comprehensive examination of the requirements for minimum levels of survival health, personal safety, livelihoods and shelter) as well. Dispossession and (public displace-ment have radically changed the landscape of human vulnerability and security. Accumulation by dispossession and displacement in various forms that associated with policies of neo-liberalization, worsen human vulnerabilities and constitute to inequalities among the people. The purpose of this paper is to analyze the main causes of development-induced displacement practiced by the people in power and how were they enforced on the vulnerable population? It is significant to establish when and how human security becomes threatened. Inadequate security, legal and economic protections may cause misappropriation of power and simultaneously victimize the people in need otherwise. Finally, what are the strategies identified by the Malaysia government to overcome the development-induced displacement caused on to the people? Ironically, Malaysia does not only faced domestic displacement but also international displacements that migrate into Malaysia for work, seek refuge and illegal migrants.